2017
DOI: 10.3892/mco.2017.1384
|View full text |Cite
|
Sign up to set email alerts
|

Re-irradiation of locoregional esophageal cancer recurrence following definitive chemoradiotherapy: A report of 6 cases

Abstract: Abstract. There is currently no consensus on salvage therapy for recurrent esophageal cancer. Salvage surgery is a well-established option for attaining long-term survival; however, it is associated with a high risk of perioperative morbidity and mortality. A total of 6 patients who underwent re-irradiation for recurrence of locoregional esophageal cancer following definitive chemoradiotherapy were investigated. The median interval between initial radiotherapy and re-irradiation was 17.4 months (range, 6.4-59.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
5
26
0
Order By: Relevance
“…In subgroup analysis, our results showed that chemotherapy combined with radiotherapy could increase survival rate. In the LD group, the median survival time for chemoradiotherapy was 14 months, which was consistent with the results reported by Katano et al [6]. However, in the HD group, chemoradiotherapy did not show better e cacy than radiotherapy alone, and other studies have reported the same [17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In subgroup analysis, our results showed that chemotherapy combined with radiotherapy could increase survival rate. In the LD group, the median survival time for chemoradiotherapy was 14 months, which was consistent with the results reported by Katano et al [6]. However, in the HD group, chemoradiotherapy did not show better e cacy than radiotherapy alone, and other studies have reported the same [17].…”
Section: Discussionsupporting
confidence: 90%
“…reported that the 1-, 2-and 3-year survival rates of 36 LRESCC patients receiving re-irradiation with concurrent chemotherapy (paclitaxel + cisplatin) were 51.7%, 21.4% and 12.2%, respectively [4]. Katano et al reported that the median survival time of six patients who underwent concurrent chemotherapy with nedaplatin and tegafur with re-radiotherapy was 13.6 months [6]. As of now, the role of chemotherapy in re-radiotherapy for recurrent ESCC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-years OS rate was 32.1% in salvage radiotherapy patients, and the median survival time was 39.0 months, which is longer than those reported in other studies [12,13]. The median ARS was 13.0 months (range 3-168 months), which was similar to the results of previous studies [11][12][13][14][15]26]. Therefore, further research is needed to improve the survival time after recurrence.…”
Section: Discussionsupporting
confidence: 78%
“…Surgery plays an important role in achieving locoregional control in patients with LR esophageal carcinoma [8] but salvage esophagectomy may cause serious surgery-related complication and hospital mortality. CRT has curative potential for LR esophageal squamous cell carcinoma (ESCC) patients, but the clinical bene t and safety is not demonstrated very well due to the small number of cases [9][10][11][12][13][14][15]. In this study, we retrospectively analyzed the e cacy and toxicity of re-irradiation (re-RT) in patients with LR after radical radiotherapy or postoperative adjuvant radiotherapy on a relative large sample.…”
Section: Introductionmentioning
confidence: 99%